2022
DOI: 10.3390/jcm11236940
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy: Let’s Step Up the Ladder of Evidence to Look Over the Horizon

Abstract: Hysterectomy is one of the most common non-obstetric gynecological surgical procedures carried out in Western countries [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In addition, the use of vNOTES may open new possible scenarios also for the treatment of malignant gynecological diseases [24]. Indeed, the Laparoscopic Approach to Cervical Cancer (LACC) trial found worse oncological outcomes in women with cervical cancer undergoing laparoscopic surgery compared with open surgery, and this raised concerns about the use of MIS for this purpose and led to an ongoing debate [25,26]. From this perspective, further studies should be aimed to investigate the role of vNOTES for gynecological cancers, in order to clarify whether this technique has similar surgical and oncological outcomes compared with other approaches [27][28][29][30][31][32][33].…”
Section: Overall Results Summarymentioning
confidence: 99%
“…In addition, the use of vNOTES may open new possible scenarios also for the treatment of malignant gynecological diseases [24]. Indeed, the Laparoscopic Approach to Cervical Cancer (LACC) trial found worse oncological outcomes in women with cervical cancer undergoing laparoscopic surgery compared with open surgery, and this raised concerns about the use of MIS for this purpose and led to an ongoing debate [25,26]. From this perspective, further studies should be aimed to investigate the role of vNOTES for gynecological cancers, in order to clarify whether this technique has similar surgical and oncological outcomes compared with other approaches [27][28][29][30][31][32][33].…”
Section: Overall Results Summarymentioning
confidence: 99%
“…In addition, most patients with EC have personal risk factors, such as obesity, diabetes or metabolic syndrome that contribute to increased surgery-related complications. Tailored surgery and no overtreatment could reduce the incidence of these adverse events [29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…There are many options surgical approach for performing hysterectomy, including abdominal, robot-assisted laparoscopic and vaginal natural orifice transluminal endoscopic surgery (vNOTES). 25 It is still controversial whether RH affects endometrial cancer outcomes. RH with bilateral salpingo-oophorectomy (BSO) is recommended for patients with stage II EC based on guidelines before 2014.…”
Section: Discussionmentioning
confidence: 99%